Comparative Anatomy of Two Mangrove Species, Xylocarpus granatum and Xylocarpus moluccensis (Meliaceae) - Chorchuhirun, Boonyawee; Kraichak, Ekaphan; Kermanee, Prasart (Thai Journal of Science and Technology, 2020)
Xylocarpus granatum and Xylocarpus moluccensis are true mangrove species, which are found in the central zone of mangrove forests. Anatomical character plays important roles to plant functions and adaptations to cope with certain environments. The plant samples were collected from the Sirinart Rajini Ecosystem Learning Center, Prachuabkirikhan province. Permanent slides of the samples were prepared using a paraffin method. The anatomical characters of root, stem, petiole, petiolule, rachis and leaf blade were examined and compared. The results showed that X. granatum and X. moluccensis shared their anatomical characters, i.e., tanniferous cells and crystals are common in both species. However, there are some different characteristics such as primary xylem in root, shape of vascular bundle in petiole, petiolule and leaf blade including number of hypodermis and palisade layers. Overall of this study, the anatomical character can discriminate between the two species.